Web-Based Information System Of Building Materials At Berkah Mandiri Pekanbaru Shop - Purjumatin; Mardiati, Dina (Journal of ICT Applications System, 2022)
Information technology is currently one of the factors that support the growth and development of a dependable company in the era of globalization, which is characterized by a level of development that is becoming increasingly advanced and modern.Toko Berkah Mandiri Pekanbaru is just one example of a building materials company that continues to process its data manually.A reliable and speedy system is needed to meet the ever-increasing demand for information.A system is good if it makes all processes easier, including computerization, which is one of them.Using MySQL as the database and the PHP programming language, this application was developed.This system or application is very helpful, especially when it comes to processing important data in a way that makes data more accurate, efficient, quick, and can save time and money